MEASUREMENT OF POVERTY - Muti’ah, Eva; Listiani, Mira; Sukma, Nasywa Nathania (LPPM Universitas Bina Bangsa, 2024)
Poverty measurement is a critical aspect of economic and social policy, providing insights into the extent and severity of deprivation within a population. Various methods and indicators have been developed to assess poverty, ranging from income-based approaches to multidimensional frameworks. Traditional poverty measurement relies on absolute and relative income thresholds, determining whether individuals or households fall below a defined poverty line. However, income alone does not fully capture the complexity of poverty, leading to the development of multidimensional poverty indices that incorporate factors such as education, health, and living standards. This study explores different methodologies used to measure poverty, highlighting their strengths and limitations. The research examines key poverty indicators, including the Headcount Index, Poverty Gap Index, and Multidimensional Poverty Index (MPI), to provide a comprehensive understanding of poverty assessment. Additionally, it discusses the role of international organizations, such as the World Bank and United Nations, in establishing global poverty measurement standards. The study also considers how economic, social, and policy-related factors influence poverty measurement outcomes. The findings underscore the importance of adopting a multidimensional approach to poverty measurement to better inform policy decisions and intervention strategies. Accurate and comprehensive poverty assessment enables governments and policymakers to design effective poverty alleviation programs tailored to specific population needs. By integrating economic and social dimensions, poverty measurement can contribute to more inclusive and sustainable development efforts.